2022
DOI: 10.1039/d2ta02887e
|View full text |Cite
|
Sign up to set email alerts
|

A novel porous graphitic carbon nitride (g-C7N3) substrate: prediction of metal-based π–d conjugated nanosheets toward the highly active and selective electrocatalytic nitrogen reduction reaction

Abstract: Two-dimensional (2D) graphitic carbon nitride skeleton offer rich hollow sites for stably anchoring transition-metal (TM) atoms to promote single-atom catalysis, which is expected to overcome a great challenge of low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…460 nm), a suitable band gap (2.7 eV), nontoxicity, and high physicochemical stability. [11][12][13][14] In addition to this, as a conjugated polymer, C 3 N 4 is composed of triazine and heptazine structural units with sp 2 hybridized carbon and nitrogen atoms. Therefore, it has a p-conjugated supermolecular network that allows for exible regulation of properties by tailoring the molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…460 nm), a suitable band gap (2.7 eV), nontoxicity, and high physicochemical stability. [11][12][13][14] In addition to this, as a conjugated polymer, C 3 N 4 is composed of triazine and heptazine structural units with sp 2 hybridized carbon and nitrogen atoms. Therefore, it has a p-conjugated supermolecular network that allows for exible regulation of properties by tailoring the molecular structure.…”
Section: Introductionmentioning
confidence: 99%
“…183) in its hexagonal crystal lattice and adopts a same lattice constant along both lattice vectors ( a = b = 9.70 Å). Just like g-C 3 N 4 , g-C 7 N 3 , and g-C 3 N, the sp 2 -hybridized g-C 10 N 3 monolayer behaves with a π–π conjugation characteristic that arises from its evenly distributed holes and abundant and uniform nitrogen coordination sites, whose π–π conjugated framework causes conducting channels and hence enhances the electronic conductivity and elevates the mechanic stability. At the same time, these periodic large holes in g-C 10 N 3 could contribute enough room, by using sp 2 -bonded N atoms, to anchor TM atoms, in which the surrounding N atoms with electron-rich lone pairs can bind to these TM atoms to avoid their migration and aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…38 Compared to their metal bulk or nanocluster counterparts, SACs, assembled by unique metal atoms as nodes and 2D support ligands as linkers, not only make maximum high-efficiency of atomic utilization but also significantly improve the activity-selectivity rooted in the low-coordination environment of these decorated atoms. 39 Especially, many SACs based on graphene-like supports consisting of different carbon and nitride stoichiometric ratio (g-C x N y ), such as Ta@g-CN, 40 W@g-C 3 N 4 , 41 Mn−V CC @g-C 3 N, 42 and W@C 9 N 4 43 have been revealed to exhibit excellent NRR catalytic performance, and some of them have even been prepared by the experimenter, which demonstrates that the g-C x N y unit is a promising substrate and an appropriate connector for TM atoms in SACs. For example, using a high-throughput screening strategy under the framework of first-principles calculation, with the "acceptance-donation" interaction, Zhang et al 43 predicted that W distributed on g-C 9 N 4 (W@g-C 9 N 4 ) can modulate the binding strength of the target adsorption intermediates, achieving an optimal NRR performance (a rather low limiting potential of −0.24 V and excellent selectivity) among 24 TM-centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both As and Sb belong to group V and have the same outer shell electron distribution. The Sb ranks below As in the periodic table, so it has better chemical stability.In addition to single-layer materials consisting of a single group, the layered binary compounds have also received increasing research attention, such as III-V, II-IV, II-VII, II-VI, III-VI, IV-V [14,[17][18][19][20][21][22][23][24][25][26][27][28][29] compounds, and single layers of group III, [27,30] group IV monochalcogenides. [31,32] Huang et al theoretically identified several possible structures for the Si x P y (y/x ≥ 1) monolayer, where the predicted A 2 B 2 -type SiP monolayer of the P-6m2 space group has a similar or even lower formation enthalpy than its bulk.…”
mentioning
confidence: 99%